2022
DOI: 10.1111/dth.15590
|View full text |Cite
|
Sign up to set email alerts
|

New onset of psoriasis following COVID ‐19 vaccination

Abstract: The cutaneous side effects of COVID‐19 vaccines are being studied and their immunogenicity is most likely linked to the pathophysiology of psoriasis. Although uncommon, several cases of exacerbation and new onset of psoriasis have been reported globally after vaccination. To contribute to the literature on this intriguing topic, we present three cases of de novo psoriasis in adult patients following COVID‐19 vaccination. Our observations and a literature review show that this occurrence is independent of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Biopsy of such lesions and microscopic evaluation of them confirmed the diagnosis of psoriasis. 78–84 Acanthosis, parakeratosis, hyperkeratosis, hypogranulation, superficial dermal lymphocytic infiltration, and rete ridge elongation were observed and consistent with guttate psoriasis. 78,81,82,85,86 In addition, Munro microabscesses and dilated capillaries in the dermal papillae were reported.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Biopsy of such lesions and microscopic evaluation of them confirmed the diagnosis of psoriasis. 78–84 Acanthosis, parakeratosis, hyperkeratosis, hypogranulation, superficial dermal lymphocytic infiltration, and rete ridge elongation were observed and consistent with guttate psoriasis. 78,81,82,85,86 In addition, Munro microabscesses and dilated capillaries in the dermal papillae were reported.…”
Section: Resultsmentioning
confidence: 79%
“…78,81,82,85,86 In addition, Munro microabscesses and dilated capillaries in the dermal papillae were reported. 78,80,84 Histopathology of a erythrodermic psoriasis lesion also revealed psoriasiform epidermal hyperplasia with loss of the granular cell layer and neutrophils in the upper layers of the overlying parakeratotic scale. 87 Meanwhile, 5 studies reported cases of pityriasis rubra pilaris, and a histopathology assessment of the lesion reported significant orthokeratosis, parakeratosis, and irregular acanthosis in the epidermis with widened rete ridges.…”
Section: Papulosquamous Lesionsmentioning
confidence: 99%
“…As regards psoriasis, a total of 98 reports on psoriasis following COVID-19 vaccination were reported. 23–54 In particular, flare of pre-existing disease and new-onset disease were reported in 81 and 17 cases, respectively. Moreover, several phenotypes of psoriasis were reported, with plaque subtype as the most frequent.…”
Section: Resultsmentioning
confidence: 99%
“…It has been elicited that IL-2, IL-12, TNF-α and IFN-γ produced by CD4+ T cells were increased after COVID-19 vaccination. 8 IL-6-induce Th17 subset of CD4+ T cells in COVID-19 immunopathology and vaccine-induced immune enhancement was highlighted by recent studies. 9 Therefore, it was speculated that COVID-19 vaccines may lead to activation of inflammatory pathways and thereby triggered psoriasis.…”
Section: Discussionmentioning
confidence: 99%